199k views
3 votes
What is the simplified form of (4j2+6)+(2j2-3)

1 Answer

5 votes

Answer:
6j^2+3

Explanation:

In order to solve this exercise it is important to remember the multiplication of signs. Notice that:


(+)(+)=+\\(-)(-)=+\\(-)(+)=-\\(+)(-)=-

In this case you have the following expression given in the exercise:


(4j^2+6)+(2j^2-3)

Where the variable is "j".

When you multiply signs, you get:


=4j^2+6+2j^2-3

Now you need to identify that like terms and then you need to add them (or combine them). So, applying this procedure you get that the simplified form of the expression is the shown below:


=6j^2+3

As you can observe, you get a 2nd degree binomial.

User Jovana
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.